<span>a³-b³=(a-b)(a²+ab+b²)
64x⁶ - 27
64 = 4³,
x⁶ = (x²)³
27 = 3³
</span>64x⁶ - 27 = 4³(x²)³ -3³ = (4x²)³ -3³. Now, we can use a formula where a=4x², b=3
(4x²)³ -3³ = (4x² -3)((4x²)² +4x²*3 + 3²) = (4x² -3)(16x⁴ +12x² + 9)
<span>
Answer: </span>64x⁶ - 27= (4x² -3)(16x⁴ +12x² + 9) <span>
</span>
Answer:
x = -1/2
Step-by-step explanation:
This question can be solved by applying the laws of indices
In a^n, a - base
n - index
Given
9^x = 1/3
According to the laws of indices, a/b = b^(-a)
Hence we can write, 1/3 = 3^(-1)
9^x = 3^(2x)
Again according to the laws of indices,
a^b = a^n can be written as;
b = n
That is, if in an equation the bases are the same, the indices are also equal.
So we can write,
3^(2x) = 3^(-1)
2x = -1
Divide both sides of the equation by 2, the coefficient of x
2x/2 = -1/2
x = -1/2
Answer:
Step-by-step explanation:
look this up it give you the answer
let me know if this help plzz